eksplorasi khamir sebagai agens biokontrol patogen blas dari filosfer daun padi sawah - selamet aswawi; Fadjar Rianto; Sarbino Sarbino (Jurnal Sains Pertanian Equator, 2019)
Blast is important disease of rice, and it caused by Pyricularia oryzae Cav. Synthetic fungicide in plant disease control may have negative impacts, so another alternative is needed. Yeast can used as a biocontrol agent. This research aims to investigate the potential of the yeast from leaf phyllosphere of rice paddy as biocontrol agent against P. oryzae. This research  was consisted of yeast exploration, isolation and filtrate antagonistic inhibition essay to P. oryzae, and yeast growth respon due to temperature. Ten isolates successfully obtained and tested as antagonist to P. oryzae. Five isolates, YLP05; YLP07; YLP08; YLP09; YLP10, have percentage inhibition more than 30% at 3 dai (day after incubation) dan more than 50% at 7 dai, but their filtrate had not shown any inhibition activity.  The five isolates had been formed colony on 1st day at 30°C.  Based on diameter and percentage of forming colony, the optimal temperature is different for each yeast isolates. Four isolates which can still grow at 20-40oC those are YPL05, YLP07, YLP09, and, YLP10.